The Use of Social Media Instagram as Instructional Media for Physics Toward Students Learning Motivation - Mahzum, Elmi; Farhan, Ahmad; Ramadhani, Eka (Universitas Syiah Kuala, 2020)
This research aims to determine the use of Instagram toward students learning motivation among class XI IPA 4 students at SMAN 2 Banda Aceh. The type of approach used in this research was qualitative. The method use of this research was experiment. the sample in this research were students of class XI IPA 4 at SMAN 2 Banda Aceh. Data collection techniques by using a learning motivation questionnaire. Analysis and data processing using a percentage equation. Based on the results and analysis of data based on the value range of the motivation level score, It was found that Instagram as a physics instructional media is beneficial to increase student motivation.Keywords: instagram, instructional media, and learning motivation